VE/VCO2 slope predicts short- and long-term outcome after anatomical pulmonary resection by VATS. (28th May 2021) - Bédat, B; Koliakos, E; Licker, M -J; Demarchi, M; Perentes, J; Triponez, F; Krueger, T; Karenovics, W; Gonzalez, M
Abstract: Objective: The ventilation-to-carbon dioxide output (VE/VCO2) slope could predict morbidity and mortality after lung resection. The aim of the study was to identify whether VE/VCO2 slope obtained from cardiopulmonary exercise test (CPET) was an independent predictor of cardiopulmonary complications after anatomical pulmonary resection by video-assisted thoracic surgery (VATS). Methods: We reviewed the files of all consecutive patients that underwent pulmonary anatomical resections by VATS between January 2010 and October 2020. The data were extracted from the registry of the Centre for Thoracic Surgery of Western Switzerland. Pneumonectomies were excluded from the study. We used a multivariable Cox regression to investigate the risk of cardiopulmonary complications associated with the VE/VCO2 slope and other possible confounders, including the Charlson Comorbidity Index (CCI), the CPET data and pulmonary functions. Results: In total, 1392 patients (mean age: 66±11 years; ratio female: 47%) underwent anatomical resection by VATS. CPET was performed in 204 patients (15%). However, the VE/VCO2 slope data were available in 145 patients, which were included for the analysis. Patients underwent segmentectomies (N = 42) and lobectomies (N = 101) mainly for lung cancer (96%). The average percentage of the predicted VO2max was of 70±17%. Maximal effort during the CPET (respiratory coefficient ratio >1.1) was not reached in 30% of patients, without impact on the VE/VCO2 slope (39±6 vs 37±7, P = 0.21). Cardiopulmonary complications appeared in 32% of patients with no mortality at 90 days. In the multivariate analysis, VE/VCO2 slope >35 was correlated with cardiopulmonary complications (OR 3.5, 95% CI [1.3-9.3], P = 0.012). CCI, pulmonary functions, peak VO2 and the extension of the anatomical resection was not associated with cardiopulmonary complications. Conclusion: VE/VCO2 slope above 35 predicts postoperative cardiopulmonary complications in anatomical resections by VATS. The VE/VCO2 slope is independent of the intensity of effort during the CPET. The impact of prehabilitation on the slope should be determined.